Teacher Without Teaching: school and teacher project for special education (1996-2016) - Kamille Vaz (Universidade Federal do Rio Grande do Sul, 2022)
The aim of this article is to contribute to the discussion on the project of public school and of teacher for Special Education as proposed by Brazilian educational policies in the beginning of the 21st century. Based on historical-dialectical materialism, we analyzed national documents that represents the Special Education policy between 1996 and 2016. We found that the public-school project is anchored in the assistance bias, with an increase in the private sector's entry into its management. Special education in the current perspective reinforces the service characteristic to be provided in regular schools, and the teacher, in this context, is one resource used, among others. Such considerations corroborate the determinations of multilateral organizations for education.